VIDEO GAME SEBAGAI REPRESENTASI ARSITEKTUR DAN PERSILANGANNYA DENGAN SEJARAH DALAM SERI ASSASSIN’S CREED - Aditya Bayu Perdana (Jurnal Arsitektur ARCADE, 2024)
Abstract: Throughout its history, abstract ideas in architecture are conveyed through representational media such as writing and drawings. Video games are among the newest medium of representation with their own unique advantage: games necessitate active participation in a virtual space that has become increasingly realistic thanks to technological advancements. This short paper aims to explore how games can be situated with other forms of architectural representation by discussing historical shifts that predated it. This paper also aims to show one of video game’s strength in representing architecture by using Assassin's Creed game series as an example case. The series shows how careful craft and detailed research on historical details within the game can create engaging and immersive architectural experience with educational value. This immersivity however is also limited by gameplay constrains and require extensive resource investment. The author hopes that this exploration could be useful stepping stone in Indonesia to expand new studies of architectural representation and exploration of more engaging learning tools.Keyword: game, architectural representation, historical setting, educational mediaAbstrak: Sepanjang sejarah, ide abstrak arsitektur disampaikan melalui sejumlah media representasional seperti tulisan dan gambar. Video game merupakan salah satu media representasi yang paling baru dengan keunikannya sendiri: game menuntut partisipasi aktif dalam ruang virtual yang semakin realistis berkat perkembangan teknologi. Tulisan singkat ini bertujuan untuk menempatkan game sebagai representasi arsitektur dengan mengulas pergeseran media representasi yang telah terjadi di masa-masa sebelumnya. Tulisan ini juga bertujuan untuk menunjukkan salah satu kekuatan media game dalam merepresentasikan arsitektur dengan menggunakan sebuah seri game berjudul Assassin’s Creed sebagai contoh kasus. Game tersebut menunjukkan bahwa kriya telaten dan riset mendalam akan detail sejarah dalam game dapat menghasilan pengalaman arsitektural yang menarik, dan imersif dengan nilai edukatif. Namun begitu imersivitas ini juga dibatasi oleh kekangan gameplay dan membutuhkan sumber daya yang tidak sedikit. Penulis berharap eksplorasi ini dapat menjadi landasan di Indonesia untuk memperluas kajian media representasi arsitektur sekaligus eksplorasi alat pengajaran yang menarik.Kata Kunci: game, representasi arsitektur, setting sejarah, media pembelajaran